Application of Pawlak’s Conflict Model to Generate Coalitions of Local Tables with Similar Values on Conditional Attributes - Przybyła-Kasperek, Małgorzata; Kusztal, Katarzyna (Wydawnictwo Politechniki Łódzkiej, 2023)
Generating a model or pattern based on dispersed data available in many different tables is difficult because there can be numerous inconsistencies in the data. One way to deal with such a problem is to analyze conflicts and generate coalitions of consistent local tables. This paper proposes a model in which coalitions of tables with consistent data are created using Pawlak’s conflict analysis approach. A model, decision tree, is created based on the aggregated data within the coalition. This way, we get rules that better describe the concepts found in consistent local tables.
Keywords: Pawlak conflict analysis model; independent data sources; coalitions; decision trees; dispersed data; model analizy konfliktu Pawlaka; niezależne źródła danych; koalicje; drzewa decyzyjne; dane rozproszone